2020
DOI: 10.1021/acs.macromol.0c00346
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the Solvent Quality on the Local Dynamics of Soft and Swollen Polymer Nanoparticles Functionalized with Polymer Chains

Abstract: Grafting polymer chains on the surface of nanoparticles (NPs) is a strategy used to control the interaction between the NPs and their environment. The fate of the resulting particles in a given environment is strongly influenced by the solvent–polymer interaction. The solvent quality affects the behavior, conformation, and dynamics of the grafted polymer chains. However, when this polymer grafting strategy is used to functionalized polymer particles, the influence of solvent quality becomes even more complex; … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 69 publications
(99 reference statements)
0
4
0
Order By: Relevance
“…In the past, the effect of water on the physical properties of NOHM-based mixtures has been explored. , It has recently been shown that the chemical and physical properties of solvents can have a significant impact on the behavior, conformation, and dynamics of nanoparticle-tethered ligands/polymers . However, there is currently a lack of understanding of how the hydrogen bonding nature, polarity, and size of the secondary fluid molecule affect relevant transport properties of ionically bound polymers in solution.…”
Section: Introductionmentioning
confidence: 99%
“…In the past, the effect of water on the physical properties of NOHM-based mixtures has been explored. , It has recently been shown that the chemical and physical properties of solvents can have a significant impact on the behavior, conformation, and dynamics of nanoparticle-tethered ligands/polymers . However, there is currently a lack of understanding of how the hydrogen bonding nature, polarity, and size of the secondary fluid molecule affect relevant transport properties of ionically bound polymers in solution.…”
Section: Introductionmentioning
confidence: 99%
“…However, controlling the aggregation state of NP in the solvent system is crucial for the formation of deposited structures after completely drying, which can be achieved through the solvent solubility. The phenomenon is particularly important for the polymer-grafted NP (also known as hair NP [HNP]). At low grafting densities, the configuration of long-chain polymer brushes grafted on the surface of NP transforms between collapse and stretching (swelling) due to changes in the solubility of the solvent components. This conformational transition affects the interactions between the HNP and solvents, thus promoting effective dispersion/aggregation. The stimulus responsiveness of HNP makes it possible to generate complex surface structures by colloidal deposition methods. One powerful technique for preparing HNP with grafting brushes capable of conformational transitions is surface-initiated atom-transfer radical polymerization (SI-ATRP), which offers precise control over the molecular weight and architecture of tethered polymers by growing polymer chains from immobilized initiators on the particle surface.…”
Section: Introductionmentioning
confidence: 99%
“…Polymer dissolution, a phenomenon driven by solvent diffusion and polymer chain disentanglement, induces full or partial miscibility of the polymer in a suitable solvent. Interaction with solvent molecules causes the polymer chains to swell, and a subsequent evaporation of the solvent typically leaves behind a roughened surface. Harnessing these fundamental insights, we have developed a versatile technique to generate uniform and spatially defined rough patches on the surfaces of non-cross-linked, smooth polystyrene (PS) microspheres.…”
mentioning
confidence: 99%